Pipeline will degrade land that we love - Rolston, Holmes, 1932-2025, author; The News Leader, publisher (Colorado State University. Libraries, 2015)
A proposed natural gas pipeline running through the Valley of Virginia and Rolston's ancestral landscape raises concerns about scarring and degrading a much-loved landscape, also about the safety of a huge steel pipeline in limestone country with many caves and sinkholes. The plans of Dominion Resources, who wish to build the line, will degrade the Old Dominion.
Keywords: Atlantic Coast Pipeline; Dominion Resources; Valley of Virginia; Shenandoah Valley; Augusta County; Hebron Presbyterian Church